Actuator disc methods for open propellers: assessments of numerical methods. Issue 1 (1st January 2017) - Bontempo, R.; Manna, M.
ABSTRACT: The paper describes the assessment of two different actuator disc models as applied to the flow around open propellers. The first method is based on a semi-analytical approach returning the solution for the nonlinear differential equation governing the axisymmetric, steady, inviscid and incompressible flow around an actuator disc. Despite its low computational cost, the method does not require simplifying assumptions regarding the shape of the slipstream, e.g. the wake contraction is not disregarded or prescribed in advance. Moreover, the presence of a tangential velocity in the wake as well as the spanwise variation of the load are taken into account. The second one is a commonly used procedure based on CFD techniques in which the effects of the propeller are synthetically described through a set of body forces distributed over the disc surface. Both methods avoid the difficulties and the computational costs associated with the resolution of the propeller blades geometrical details. The comparison is based on an in-depth error analysis of the two procedures which results in a set of reference data with controlled accuracy. An excellent agreement has been documented between the two methods while the computational complexity is obviously very different. Among other things the comparison is also aimed at verifying the accuracy of the semi-analytical approach at each point of the computational domain and at quantifying the effect of the errors embodied in the two methods on the quality of the solution, both in terms of global and local performance parameters. Furthermore, the paper provides a set of reference solutions with controlled accuracy that could be used for the verification of new and existing computational methods. Finally, the computational cost of the semi-analytical model is quantified, thus providing a valuable information to designers who need to select a cost effective and reliable analysis tool.